2019
DOI: 10.3390/app9153109
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Commercial Biochar Fillers on Brittleness/Ductility of Epoxy Resin Composites

Abstract: Production of versatile composites is a very attractive field. Carbon containing epoxy resins are one of the most relevant reinforced plastics used for a wide number of applications. In this research, we studied the influence of five different commercial biochar samples for the selective enhancement of brittleness and ductility of an epoxy based composite. We proved the relationship between biochar morphology and composites mechanical properties with the aid of FT-IR and FE-SEM analysis. We were able to improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
42
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1
1

Relationship

6
3

Authors

Journals

citations
Cited by 52 publications
(44 citation statements)
references
References 31 publications
2
42
0
Order By: Relevance
“…Coffee wastes have been also used as feedstock for pyrolytic conversion producing hydrogen-rich gas [8] and fuel-quality biochar [9]. Biochar has been used not only as solid fuel but also as high performance material [10,11], as a flame retardant additive [12,13], for electrochemical [14] and energy storage applications [15] and for production of composites [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Coffee wastes have been also used as feedstock for pyrolytic conversion producing hydrogen-rich gas [8] and fuel-quality biochar [9]. Biochar has been used not only as solid fuel but also as high performance material [10,11], as a flame retardant additive [12,13], for electrochemical [14] and energy storage applications [15] and for production of composites [16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…reported the use of high thermal treated biochar for the production of conductive epoxy composite while other studies reported the improvement of mechanical properties of biochar containing reinforced plastics . Recently, Bartoli et al . described the influence of biochar surface structures on brittleness or ductility of epoxy materials showing how smooth surface could enhance the maximum elongation.…”
Section: Introductionmentioning
confidence: 99%
“…Also, coffee wastes have been used as feedstock for pyrolytic conversion producing hydrogen rich gas [8] and fuel quality biochar [9]. Biochar has been used not only as sold fuel but also as high performance material [10,11] for electrochemical [12] and energy storage applications [13], and for composites production [14][15][16].…”
Section: Introductionmentioning
confidence: 99%